Contagious bovine and caprine pleuropneumonia: A research community’s recommendations for the development of better vaccines - Jores, Joerg; Baldwin, Cynthia L.; Blanchard, A.; Browning, G.F.; Colston, A.; Gerdts, V.; Goovaerts, D.; Heller, M.; Juleff, N.; Labroussaa, F.; Liljander, Anne M.; Muuka, G.; et al. (Springer, 2020)
Contagious bovine pleuropneumonia (CBPP) and contagious caprine pleuropneumonia (CCPP) are major infectious diseases of ruminants caused by mycoplasmas in Africa and Asia. In contrast with the limited pathology in the respiratory tract of humans infected with mycoplasmas, CBPP and CCPP are devastating diseases associated with high morbidity and mortality. Beyond their obvious impact on animal health, CBPP and CCPP negatively impact the livelihood and wellbeing of a substantial proportion of livestock-dependent people affecting their culture, economy, trade and nutrition. The causative agents of CBPP and CCPP are Mycoplasma mycoides subspecies mycoides and Mycoplasma capricolum subspecies capripneumoniae, respectively, which have been eradicated in most of the developed world. The current vaccines used for disease control consist of a live attenuated CBPP vaccine and a bacterin vaccine for CCPP, which were developed in the 1960s and 1980s, respectively. Both of these vaccines have many limitations, so better vaccines are urgently needed to improve disease control. In this article the research community prioritized biomedical research needs related to challenge models, rational vaccine design and protective immune responses. Therefore, we scrutinized the current vaccines as well as the challenge-, pathogenicity- and immunity models. We highlight research gaps and provide recommendations towards developing safer and more efficacious vaccines against CBPP and CCPP.